PERANCANGAN RUSUNAWA DI DENPASAR BARAT - I Wayan Sukerta; I Nyoman Gde Suardana (Universitas Dwijendra, 2017)
Bali is an island that is well known in the national and international. Bali's natural culture and customs that have traditionally become Balinese spirit so that they can be known as today. Many preferred destinations can be visited by tourists. ranging from nature tourism, marine tourism, cultural tourism, culinary, religious, agro tourism etc. Foreign tourist arrivals in 2015 reached 363.8 visits up 6.65 percent compared to 2014.Â The progress of an area like Bali is inseparable from the impact of these developments. Several problems began to emerge, such as an increase in population, neighborhoods and settlements. Settlements are an important thing that needs attention. In Bali, the city of Denpasr in particular is a city that becomes the destination of migrants to change their destiny.The city of Denpasar is the capital of Bali province, similar to the problems experienced by other big cities, one of which is in the field of housing and settlement. The high price of land and some other supporting facilities also increase. So what happens in the community is the difficulty of having a decent home. Thus the need for simple apartment rental (rusunawa)Rusunawa is one type of dwelling that is very feasible in applied in Bali, Denpasar City in particular. The most basic reason for this is that apartment buildings can accommodate quite a lot of occupants, fewer land uses, the construction can be done vertically and maximally, can support a better urban environmental arrangement and can be owned by rental system without having to be in charge of building maintenance.Keywords: rusunawa, denpasar city